TRANSCATHETER AORTIC VALVE IMPLANTATION AND OPEN AORTIC SURGERY: COMPARATIVE ASSESSMENT OF RESULTS - V. I. Ganyukov; R. S. Tarasov; I. E. Vereshchagin; N. A. Kochergin; A. N. Stasev; O. A. Nagirnyak; L. S. Barbarash (Евразийский Кардиологический Журнал, 2018)
Aim. The aim of this study is to compare hospital and long-term outcomes in patients with low surgical risk after aortic stenosis correction in surgical aortic valve replacement (SAVR) and transcatheter aortic valve implantation (TAVI).Materials and methods. Patients with aortic stenosis (AS) were included in the study. The main criterion for inclusion - the presence of indications for surgical correction of an isolated aortic valve defect. The first group included patients after TAVI (n = 11). As a control group, patients who underwent surgical correction aortic stenosis (n = 23). The TAVI group used non-repositories CoreValve (Medtronic) and repositioned Lotus (Boston Scientific) valves. Biological prosthesis Uniline (KemKor) was used in the group of surgical patients. The efficacy of the interventions was evaluated at the hospital and annual follow-up, based on the analysis of the combined endpoint, and major adverse cardiovascular events.Results. The mean age of the patients was 66.9±5.7 years in the SAVR group and 75.3±4.1 years in the TAVI group (р=0,003). The average score for EuroSCORE II was 3.49±0.3 in the SAVR group and 3.93±1.2 in the TAVI group (р=0,31). Repositionable and non-repositionable valves were implanted in 2 and 9 cases, respectively. The combined endpoint was noted in one patient in the TAVI group and in four patients in the SAVR group according to the annual observation results. There are three (13%) fatal outcomes in the surgical prosthesis group.Conclusion. The possibility of using TAVI in low-risk patients with aortic stenosis was demonstrated on the basis of comparable results of evaluating efficacy and safety with SAVR in 1-year follow-up.